Money and Biased Technical Progress: A Further. Test on 'Monetization as Technological Innovation' Hypothesis - Habibullah, Muzafar Shah (Universiti Putra Malaysia Press, 1993)
Recent studies have tested the hypothesis of 'monetization as technological innovation' for the Indian economy. The objective of this paper is to test the above hypothesis on the the Malaysian rubber estate sector data over the period 1962-89. We seek to determine the bias in technical change on labor and capital in the rubber estate sector economy. In this study, we use both the conventional and the error correction model of production function. Results indicate that the total bias in technical change is labor saving. The study further points out that the failure to appropriately allow for non-stationary il1legrated variables in estimation has led lO estimates which are subjected to substantial upward bias.